1990
DOI: 10.1002/ijc.2910460319
|View full text |Cite
|
Sign up to set email alerts
|

Are energy and energy‐providing nutrients related to exocrine carcinoma of the pancreas?

Abstract: During 1984-88 a population-based case-control study was carried out in The Netherlands in collaboration with the International Agency for Research on Cancer in order to further explore the possible relationship between diet and exocrine pancreatic carcinoma. Past habitual dietary intake was assessed in 164 cases and 480 controls. This is the first series of population-based studies of pancreas cancer to perform a comprehensive assessment of diet. The results of logistic regression analysis, controlled for age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 33 publications
(39 reference statements)
4
39
3
Order By: Relevance
“…One case -control study (Zatonski et al, 1991) in Poland found a strong decrease in pancreatic cancer risk (OR ¼ 0.10; P-trend ¼ 0.02) with higher monounsaturated fat intake. Another case -control study (Bueno de Mesquita et al, 1990) in the Netherlands reported a 60% nonsignificant decrease in risk among men, but not among women. Other studies have detected no statistically significant association with monounsaturated FAs (Howe et al, 1990;Michaud et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One case -control study (Zatonski et al, 1991) in Poland found a strong decrease in pancreatic cancer risk (OR ¼ 0.10; P-trend ¼ 0.02) with higher monounsaturated fat intake. Another case -control study (Bueno de Mesquita et al, 1990) in the Netherlands reported a 60% nonsignificant decrease in risk among men, but not among women. Other studies have detected no statistically significant association with monounsaturated FAs (Howe et al, 1990;Michaud et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Although no association with total or saturated fat intake has been found (Farrow and Davis, 1990;Kalapothaki et al, 1993), a significant decrease in risk with higher saturated (Bueno de Mesquita et al, 1990Zatonski et al, 1991;Ji et al, 1995;Silverman et al, 1998), monounsaturated (Bueno de Mesquita et al, 1990;Zatonski et al, 1991), and polyunsaturated (Zatonski et al, 1991) fat intake has been reported. A recent cohort study found no significant association in relation to specific FAs (Michaud et al, 2003), but included less than 180 cases over 18 years of follow-up.…”
mentioning
confidence: 99%
“…Overall six case -control (Bueno de Mesquita et al, 1990;Howe et al, 1990;Ghadirian et al, 1991;Zatonski et al, 1991;Silverman et al, 1998;Hanley et al, 2001) and eight cohort studies (Friedman and van den Eeden, 1993;Shibata et al, 1994;Gapstur et al, 2000;Michaud et al, 2001;Stolzenberg-Solomon et al, 2002;Calle et al, 2003;Lee et al, 2003) were eligible for inclusion in this metaanalysis. In total, these studies included 6391 cases of pancreatic cancer ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The observed inverse associations between increased mono-and disaccharide intake and pancreatic cancer risk in men became less pronounced, whereas all other findings remained the same. Eight studies have examined the intakes of simple (monosaccharide and disaccharide) sugars (34,41,42), refined sugars (35), or sucrose (14 -16, 32, 42). Of these studies, just a few found an increased risk of pancreatic cancer (35,41).…”
Section: Discussionmentioning
confidence: 99%